Теоретичні аспекти сутності доходів та їх класифікація - Яворська, Тетяна Іванівна; Яворская, Татьяна Ивановна; Yavorska, Tetiana; Соболевська, О. О. (My University, 2020)
UK: Розглянуто економічну сутність категорії "дохід". Проаналізовано різні економічні підходи щодо визначення поняття «дохід підприємства». Досліджено існуючі класифікації доходів підприємства з акцентом на бухгалтерський та управлінський рівні. EN: The most important and key indicator of the enterprise is the income received, which depends on the possibility of existence, operation of the enterprise, its competitiveness and financial condition. The study of this category showed many contradictions and differences in its interpretation. Therefore, it is important to understand and find the most universal, acceptable for all purpose’s definition of "enterprise income". The results of the study. Acquaintance with the theoretical works of foreign and domestic economists, indicate the lack of a single, generally accepted definition of "income". Even today, the concept of the category "income" remains controversial and uncertain. For the most part, the concept of "income" has no distinction from the concept of "profit" and is identified with such as: "income", "total income", "gross income", "net income", "entrepreneur's income", "in-come" on capital ”,“ financial result ”,“ gross profit ”,“ net profit ”,“ balance sheet profit ”,“ profit ”, etc.: The con-cept of“ enterprise income ”is a component of the category“ income ”and also has different interpretations as in science , and at the legislative level, and is considered by modern scientists as the amount of revenue from sales of products and property, as well as from the implementation of nonoperating activities. The logical and structured classification of the company's income fully reveals the socio-economic content and allows to make effective decisions on their management. Conclusions. The study showed that based on the analysis of publications on the issue of income in scientific papers, there is no single approach to the definition of economists at any time and in different areas of the essence of this category. To implement the effective operation of the enterprise it is important to understand and find the most univer-sal, acceptable for all purposes, the concept of "enterprise income" and the sources of its formation. It should give a clear understanding of the essence of the income of the enterprise, which in the process of its activities seeks to reduce the unpredictability of the future by justifying its decisions taking into account past and present trends.
Theoretical aspects of the essence of income and their classification
Keywords: дохід; дохід підприємства; прибуток; виручка від реалізації; income; enterprise income; profit; sales revenue; income classification